2001
DOI: 10.1073/pnas.98.4.2041
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging evidence implicating cerebellum in the experience of hypercapnia and hunger for air

Abstract: Recent neuroimaging and neurological data implicate cerebellum in nonmotor sensory, cognitive, vegetative, and affective functions. The present study assessed cerebellar responses when the urge to breathe is stimulated by inhaled CO2. Ventilation changes follow arterial blood partial pressure CO2 changes sensed by the medullary ventral respiratory group (VRG) and hypothalamus, entraining changes in midbrain, pons, thalamus, limbic, paralimbic, and insular regions. Nearly all these areas are known to connect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 53 publications
4
51
2
1
Order By: Relevance
“…The factor ''sense of suffocation'' arises mainly from the stimulation of chemoreceptors [Meek and Schwartzstein, 1999] and involves the activation of the limbic/paralimbic and cerebellar regions [Banzett et al, 2000;Corfield et al, 1995;Evans et al, 2002;Liotti et al, 2001;Parson et al, 2001]. In our study, the CO 2 -induced panic attacks were linked to high factor scores for sense of suffocation, but this link disappeared after patients were subgrouped according to the similarity of CO 2 responses to their unexpected panic attacks.…”
Section: Discussioncontrasting
confidence: 61%
“…The factor ''sense of suffocation'' arises mainly from the stimulation of chemoreceptors [Meek and Schwartzstein, 1999] and involves the activation of the limbic/paralimbic and cerebellar regions [Banzett et al, 2000;Corfield et al, 1995;Evans et al, 2002;Liotti et al, 2001;Parson et al, 2001]. In our study, the CO 2 -induced panic attacks were linked to high factor scores for sense of suffocation, but this link disappeared after patients were subgrouped according to the similarity of CO 2 responses to their unexpected panic attacks.…”
Section: Discussioncontrasting
confidence: 61%
“…The cerebellum, which receives vagal inputs (24), plays an essential role in coordinating sensory aspects of loads with respiratory motor output. It has been reported that respiratory loading tasks are associated with activation of the cerebellum (11,20,27,35,46,47), as in our study. Parietal lobules are somatosensory association areas and are particularly concerned with vigilance.…”
Section: Activation In Cortical and Subcortical Regions Associated Wisupporting
confidence: 74%
“…Indeed, activation of these structures in response to respiratory challenges has been previously reported (5,8,11,31,35,47). The prefrontal cortex, including the middle and inferior frontal gyri, was also activated during respiratory challenge, as in previous studies (5,11,31,46). The cerebellum, which receives vagal inputs (24), plays an essential role in coordinating sensory aspects of loads with respiratory motor output.…”
Section: Activation In Cortical and Subcortical Regions Associated Wimentioning
confidence: 61%
“…Interestingly, breath holding was not associated with increased activity within the cerebellum; cerebellar activity is commonly reported in human respiratory related imaging paradigms (Evans et al, 2002;McKay et al, 2003;Parsons et al, 2001) and in animals (Xu and Frazier, 2002) usually when task-related respiratory motor activity is increased.…”
Section: Discussionmentioning
confidence: 83%